Respuesta :

Answer:

Step-by-step explanation:

An exponent raised to a negative number can be re-written with the following pattern:

X^-Y = 1/(X^Y)

So the equation you gave can be rewritten as:

[2/(x^2)]*[1/(y^2)] = [2/(3^2)]*[1/(2^2)] = (2/9)*(1/4) = 2/36 = 1/18

Answer:

(assuming you are looking for the answer letting x=3 and y=-2)

2x^-2=2/9

y^-2=-1/4

Step-by-step explanation:

It seems like you have 2 different equations there. Them being 2x^-2 and y^-2 because the two equations aren't connected.

If this is the case you simply substitute and solve!